The Role Of Youth in the Development Program Of Business Entities Owned By Bah Butong Village Sidamanik Subdistrict Simalungun Regency - Eriza Hudori; Erika Revida; Beby Karina Fawzea Sembiring (Publisher Cv. Inara, 2021)
The purpose of this study is to analyze the role of youth in Bah Butong Village,Sidamanik Subdistrict, Simalungun Regency in the Improvement of The Program of Business Entities Owned by Bah Butong Village, Sidamanik Subdistrict, Simalungun Regency. This research focuses on the role that has been done by the youths in Bah Butong Village, Sidamanik Subdistrict, Simalungun Regency in improving the program of Bah Butong Village Owned Enterprises in Sidmanik Subdistrict, Simalungun Regency. In Bah Butong Village there are BUMDes that focus their activities in the field of services, namely party equipment rental, trade, livestock, small industry, ATV rental services, keyboard rental, village transportation rental. For the development of BUMDes institutions, it is necessary to improve programs involving youth, communities and the simalungun district government. The method used in this study is descriptive method with qualitative approach. This study took primary data through informants and secondary data from related agencies, namely the Head of The Youth Sports and Tourism Office Kabupaten Simalungun,Chairmanof KNPI Simalungun,and Head of the Central Statistics Agency of Simalungun Regency, .The results of the research showed that the role of youth of Bah Butong Village Sidamanik Subdistrict Simalungundalam in the Improvement of BUMDes Bah Butong Program to market ponot waterfall tourism for regional development is with youth acting as social control, moral strength and agent of change where the role is influenced by internal factors, namely: finance, poor management, lack of support from the elderly and lack of control over every activity bumdes Bah Butong and external factors, namely: low level of education, lack of awareness in managing existing natural potential well and natural disasters